HYBRID IJTIHĀD AND THE DILEMMA OF PUBLIC INTEREST: THE DYNAMICS OF APPLYING IJTIHĀD THEORY IN MUI FATWAS ON UNREGISTERED MARRIAGES AND CHILD MARRIAGES - Amin, Mukhlisah; Dwi Widyanti Putri (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2026)
Purpose - This study examines the practical application of theories of ijtihad in the fatwas of the Indonesian Ulema Council (MUI), focusing on the issues of unregistered marriages and child marriage, as well as their impact on the diversity of legal arguments and the consistency of fatwa outcomes. Additionally, this study evaluates the extent to which the maqāṣid al-sharī‘ah approach is operationalized in addressing contemporary social problems. Methods - This study is a literature review employing a normative-doctrinal approach. The primary data included MUI Fatwa No. 10 of 2008 on unregistered marriages and the 2009 Ijtima’ Ulama Decision on child marriage. Analysis was conducted using content analysis and critical interpretation of the fatwa text, supported by classical fiqh literature, contemporary usūl al-fiqh, and the maqāṣid al-sharī’ah framework. Findings - This study found that the MUI applies a hybrid approach that combines taqlīd toward classical fiqh and collective ijtihād based on considerations of the public interest. Although the MUI acknowledges the negative social impacts of unregistered and underage marriages, its fatwas continue to sanction these practices based on the opinions of classical Islamic scholars, resulting in key concepts such as harm, maturity, and the public interest not being defined with sufficient clarity. Consequently, the application of maqāṣid al-sharī’ah in fatwas tends to be normative-formalistic and insufficiently responsive to the complexities of contemporary reality. Contributions/limitations of the study - This study contributes to the discussion of Islamic legal reform by critically evaluating the methodology of MUI fatwas. The study’s limitation is its reliance on secondary data without empirical field research. Originality/value - This study offers an original analysis of the application of ijtihād and maqāṣid al-sharī’ah theories and underscores the urgency of a more dynamic and contextual approach to Islamic law.